Effects of α-Lipoic Acid on Phagocytosis of Oligomeric Beta-Amyloid1–42 in BV-2 Mouse Microglial Cells - Ko, Chih-Yuan; Xu, Jian-Hua; Chang, Yu-Wei; Lo, Yangming Martin; Wu, James Swi-Bea; Huang, Wen-Chung; Shen, Szu-Chuan (Frontiers in Aging Neuroscience, 2022)
Background and Objectives: This study aimed to investigate the enhancing effect of vitamin-like α-lipoic acid (ALA) on phagocytosis of oligomeric beta-amyloid (oAβ1-42) in BV-2 mouse microglial cells. Methods: An in vitro model was established to investigate phagocytosis of oAβ1-42 in BV-2 cells. Transmission electron microscopy images indicated that the morphology of prepared oAβ1-42 was spherical particles. BV-2 cells treated with ALA were incubated with 5(6)-carboxyfluorescein-labeled oAβ1-42 (FAM-oAβ1-42) for 24 h, followed by flow cytometer analysis, western blotting, real-time quantitative PCR, and immunocytochemistry (ICC) analysis to assess the in vitro phagocytosis of oAβ1-42. Results: ALA significantly increased mRNA expression of the CD36 receptor in BV-2 cells. ICC analysis showed that ALA significantly elevated CD36 protein expression in BV-2 cells both with or without oAβ1-42 treatment. Results from the flow cytometry analysis indicated that the CD36 receptor inhibitor significantly attenuated ALA-promoted phagocytosis of FAM-oAβ1-42 in BV-2 cells. Moreover, ICC analysis revealed that ALA caused the translocation of peroxisome proliferator-activated receptor (PPAR)-γ, which is known to regulate the expression of CD36 mRNA, in BV-2 cells. ALA also elevated both mRNA and protein expression of cyclooxygenase-2 (COX-2), which is a key enzyme involved in the synthesis of 15-deoxy-△12,14- prostaglandin J2, in BV-2 cells. Conclusions: We postulate that ALA enhances oAβ1-42 phagocytosis by up-regulating the COX-2/15-deoxy-△12,14-prostaglandin J2/PPAR-γ/CD36 pathway in BV-2 cells, however future study should be conducted with an in vivo study to confirm the findings.